Buyang Huanwu decoction increases the expression of glutamate transporter-1 and glutamate synthetase in association with PACAP-38 following focal ischemia - DING, WENTING (Biomed Rep, 2015)
The neuroprotective role of Buyang Huanwu decoction (BYHWD) in focal ischemia is associated with decreasing glutamate concentration. However, the mechanisms are not fully understood. The present study aimed to explore whether glutamate transporter-1 (GLT-1) and glutamine synthetase (GS) participated in the decreased level of glutamate and whether pituitary adenylate cyclase-activating polypeptide-38 (PACAP-38) was involved in this process. BYHWD was found to significantly upregulate the expression of GLT-1 and GS in the hippocampal CA1 area compared to the ischemia group, with the difference on day 3 being most significant. BYHWD increased the level of PACAP-38, and PACAP-(6–38) (PACAP receptor antagonist) significantly attenuated the effect of BYHWD on GLT-1 and GS, suggesting that PACAP-38 was involved in the upregulation of GLT-1 and GS induced by BYHWD. In addition, as GLT-1 and GS are mainly located in astrocytes, the changes of astrocytes were detected by glial fibrillary acidic protein (GFAP; an astrocytic marker) immunostaining. The results showed that BYHWD inhibited the expression of GFAP compared with the ischemia group, however, co-administration with PACAP-(6–38), which inhibited the effect of BYHWD on GLT-1 and GS in astrocytes, attenuated this effect, indicating that astrocytes participated in the protective role of BYHWD following focal ischemia. These results provided the evidence for the first time that not only neurons but also astrocytes contribute to the protective role of BYHWD, which opposes previous studies and may be a starting point for traditional medicine.